Unfair Labor? : American Indians and the 1893 World's Columbian Exposition in Chicago - Beck, David, 1956- (Book collections on Project MUSE., 2019)
"Unfair Labor? breaks new ground by telling the stories of individual laborers, naming names, and uncovering the untold story of the roles that Native Americans involved in the 1893 World's Fair played in the changing economic conditions of tribal peoples and redefining their place in the American socioeconomic landscape"--